Brain activity during landmark and line bisection tasks - Cicek, Metehan; Deouell, Leon Y.; Knight, Robert T. (Frontiers in Human Neuroscience, 2009)
Neglect patients bisect lines far rightward of center whereas normal subjects typically bisect lines with a slight leftward bias supporting a right hemisphere bias for attention allocation. We used fMRI to assess the brain regions related to this function in normals, using two complementary tasks. In the Landmark task subjects were required to judge whether or not a presented line was bisected correctly. During the line bisection task, subjects moved a cursor and indicated when it reached the center of the line. The conjunction of BOLD activity for both tasks showed right lateralized intraparietal sulcus and lateral peristriate cortex activity. The results provide evidence that predominantly right hemisphere lateralized processes are engaged in normal subjects during tasks that are failed in patients with unilateral neglect and highlight the importance of a right fronto-parietal network in attention allocation.